Singlet fission materials for improved solar cells - Heng, Zhi Yin (Nanyang Technological University, 2021)
This project report focuses on the chemical synthesis and characterization of organic compounds to determine its capability in exhibiting singlet fission phenomenon, which will in turn lead to an enhancement of solar cell efficiency when used in organic photovoltaic cells. Various chemical synthesis methods, such as Grignard synthesis, Friedlander synthesis, and Suzuki coupling reactions, are employed to obtain the desired compound 5: 1,4-bis(8,14-diphenyldibenzo[b,j][1,7]phenanthroline-11-yl)benzene. All compounds obtained are characterized by nuclear magnetic resonance (NMR) spectroscopy. From the H-NMR spectroscopy, it can be observed that compound 5 has been obtained through the Suzuki coupling. However, further verification is needed through other characterization methods, such as UV-Vis and Fluorescence spectroscopy, and Mass spectroscopy, as C-13 NMR result was unable to be obtained due to the low solubility of compound 5.